2012
DOI: 10.1212/wnl.0b013e3182661fe3
|View full text |Cite
|
Sign up to set email alerts
|

PRRT2phenotypes and penetrance of paroxysmal kinesigenic dyskinesia and infantile convulsions

Abstract: PRRT2 mutations are the major cause of PKD or ICCA, but they do not seem to be involved in the etiology of febrile convulsions and migraine. The identification of PRRT2 as a major gene for the PKD-ICCA-BFIC spectrum allows better disease classification, molecular confirmation of the clinical diagnosis, and genetic testing and counseling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
70
2
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(75 citation statements)
references
References 33 publications
1
70
2
2
Order By: Relevance
“…The most common c.649_650insC mutation has been identified in a majority of families with BIE and/or PKD [4][5][6][7][9][10][11][12][13][16][17][18]. Age at the onset and offset of epilepsy was variable among individuals even within a single family with c.649_650insC mutation [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common c.649_650insC mutation has been identified in a majority of families with BIE and/or PKD [4][5][6][7][9][10][11][12][13][16][17][18]. Age at the onset and offset of epilepsy was variable among individuals even within a single family with c.649_650insC mutation [5].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Heron et al identified five different mutations in PRRT2 in 14 of 17 families affected by BIE and in five of six families affected by ICCA [5] and Ono et al found two mutations in PRRT2, c.649_650insC and c.748C>T, in all individuals with PKD and/or BIE [6]. Thereafter, several reports have shown that PRRT2 mutation will be one of the major genes relating to BIE, PKD, and ICCA [7][8][9][10][11][12][13][14][15][16][17][18][19][20]. However, we hypothesized that PRRT2 mutation may also be related to several phenotypes of infantile epilepsies other than BIE and/or PKD.…”
Section: Introductionmentioning
confidence: 99%
“…The high prevalence of migraine in the general population may, however, explain why co-segregation is not always found [44].…”
Section: Familial Hmmentioning
confidence: 99%
“…Several of these mutations have been demonstrated to cause altered cellular localisation of the PRRT2 protein or loss of detectable protein expression in vitro 4 28. Fifteen different missense mutations have been reported 22–25 29 34 35 37 42 45 46 50 54. These alter amino acid residues clustered in and around two putative transmembrane domains located near the C-terminus of the protein (table 1, figure 2A).…”
Section: Identification Of Mutations In Prrt2mentioning
confidence: 99%